Revealing the impact of students' anxiety and fear during public speaking performances: A perspective from the theory of language development - Dewi Puspitasari; Ocid Abdul Rosyid; Aulia Amini; Boma Rizki Fitriantoro (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
This study explores students' experiences of anxiety and fear when engaging in public speaking and examines the impact of these emotions on language development. Despite the importance of public speaking in personal, academic, and professional domains, many students face challenges of anxiety and fear. Understanding how these emotions (affect) language development is crucial for teaching practices. Drawing on the theory of language development, this study aims to investigate students' anxiety and fear during public speaking and their language development processes. Through in-depth interviews and participant observations, the study seeks to capture students' perspectives and experiences in relation to their anxiety and fear. The qualitative analysis explored the nature and manifestations of the two, focusing on factors such as fear of judgment, self-consciousness, and performance anxiety. The research findings contribute to a deeper understanding of the complex interplay between anxiety, fear, and language development in the context of public speaking. This study provides valuable insights to inform possible instructional strategies. Recommendations based on the theory of language development highlight the importance of creating supportive and inclusive learning environments, implementing targeted interventions, and fostering students' self-confidence in public speaking contexts